Glycemic Status During Different Trimester of Pregnancy (KYAMC Journal, 2017)
Gestational diabetes mellitus (GDM) and impaired glucose tolerance (IGT) during pregnancy cause significant fetal and maternal morbidity. Evaluation of glycemic status throughout the pregnancy especially during second and third trimesters is of paramount importance to detect GDM and IGT cases. This can help taking appropriate control measures and to avoid unwanted feto-maternal outcomes. The focus of this research is to understand variation of glycemic status at different trimester and generate a baseline data for Bangladesh using a case study. A total of 300 pregnant women at different trimester of pregnancy were recruited for the study. Plasma glucose levels both fasting and post prandial were done by standard laboratory procedure in all pregnant women included in this study. Glycosylated haemoglobin (HbA1C) level of all pregnant women were also estimated and expressed in percentage (%). Out of 300 pregnant women 57% were in 3rd , 32% were in the 2nd and 11 % were in the 1st trimester. The results found 3%, 6.3% and 4.1% pregnant women in the 1st, 2nd and 3rd trimester respectively had significantly raised level of postprandial blood sugar (PPBS) and HbA1c levels with cumulative prevalence of 4.7%. This finding is consistent with the range of GDM as per World Health Organization (WHO) estimates in different population study. The finding from this research will be beneficial to understand the risk for GDM implement patient screening plan to work effectively in Bangladesh.KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 791-794